2015
DOI: 10.1108/bfj-12-2014-0392
|View full text |Cite
|
Sign up to set email alerts
|

Designing geographical indication institutions when stakeholders’ incentives are not perfectly aligned

Abstract: Purpose – Geographical Indications (GI) are complex and multi-purpose institutions. Their objectives include encouraging diversification of agricultural production, improving farmers’ income, countering depopulation of rural areas, satisfying consumer demand for high-quality good, and protecting consumers from food fraud. The authors argue that such objectives are not necessarily aligned as divergence may arise among stakeholders (such as farmers, consumers or rural communities) about the optimal design of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
0
12
0
6
Order By: Relevance
“…In spite of the large body of theoretical literature on food labels (see Bonroy and Constantatos (2015) for a review), only a few studies focus specifically on food fraud (Giannakas 2002; Hamilton and Zilberman 2006; Baksi and Bose 2007; Di Fonzo and Russo 2015). Some of these works found that third‐party certification can lower the incidence of fraud, preventing consumers' welfare losses and reducing inspection costs (Giannakas 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the large body of theoretical literature on food labels (see Bonroy and Constantatos (2015) for a review), only a few studies focus specifically on food fraud (Giannakas 2002; Hamilton and Zilberman 2006; Baksi and Bose 2007; Di Fonzo and Russo 2015). Some of these works found that third‐party certification can lower the incidence of fraud, preventing consumers' welfare losses and reducing inspection costs (Giannakas 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This result holds even when certification is costly as long as certification cost offsets the ‘incentive‐to‐cheat' (Baksi and Bose 2007) leading to the number of firms selling products with credence attributes being inversely related to the incentive of mislabelling (Hamilton and Zilberman 2006). The study by Di Fonzo and Russo (2015) who study GI consortia creation find instead that under certain conditions, labelling fraud can be rationally tolerated by all the other consortium members.…”
Section: Introductionmentioning
confidence: 99%
“…Fraud is rarely analysed in markets characterised by common reputation and ‘nested names’, where firms simultaneously adopt a private brand and collective label(s) such as labels of Geographic Indication (GIs) (Moschini et al , Menapace & Moschini , Yu et al , Di Fonzo and Russo ). In such markets, establishing a collective reputation brand allows for vertical differentiation or, at least, a minimum quality standard.…”
Section: Asymmetric Information Food Fraud and Food Labellingmentioning
confidence: 99%
“…However, some suggest that without strict regulation, mislabelling fraud is possible. Di Fonzo and Russo () explicitly model GI consortia formation, allowing consortium members to engage in fraud. Notably, these authors find as long as there is a positive probability, frauds go undetected, and if punishment is not perfect, then defecting firms prefer using the consortia label and commit fraud rather than not using the GI.…”
Section: Asymmetric Information Food Fraud and Food Labellingmentioning
confidence: 99%
See 1 more Smart Citation